2020
DOI: 10.1016/j.jpedsurg.2020.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-rich saline protects intestinal epithelial tight junction barrier in rats with intestinal ischemia–reperfusion injury by inhibiting endoplasmic reticulum stress-induced apoptosis pathway

Abstract: Aim: To investigate the effects of hydrogen-rich saline (HRS) on intestinal epithelial tight junction (TJ) barrier in rats with intestinal ischemia-reperfusion injury (IIRI). Materials and methods: Thirty-two healthy male Sprague-Dawley (SD) rats were randomly divided into four groups (n = 8 each): Sham group, I/R group, HRS group and 4-PBA group. After 45 min of ischemia and 6 h of reperfusion, the rats were sacrificed to collect serum and ileum for detection. Hematoxylin and eosin (H&E) staining was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…A growing body of literature has shown that both oxidative and ER stress contribute significantly to epithelial damage during intestinal I/R injury (Bi et al, 2020;Ding et al, 2020;Hartmann et al, 2017;Liu et al, 2019). As a result, oxidative stress in the ER caused by intestinal I/R accelerates the accumulation of unfolded and misfolded proteins, ultimately leading to apoptosis (Jiang et al, 2020;Yin et al, 2020;Yoo et al, 2019). Consistently, in the current study, we found that remifentanil significantly suppressed intestinal I/R-induced oxidative stress, as evidenced by decreased intestinal mucosal MDA and increased intestinal mucosal SOD levels, as well as downregulated ER stress, as evidenced by the decreased mRNA and protein expressions of Bip, CHOP, caspase-12, and cleaved caspase-3 in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature has shown that both oxidative and ER stress contribute significantly to epithelial damage during intestinal I/R injury (Bi et al, 2020;Ding et al, 2020;Hartmann et al, 2017;Liu et al, 2019). As a result, oxidative stress in the ER caused by intestinal I/R accelerates the accumulation of unfolded and misfolded proteins, ultimately leading to apoptosis (Jiang et al, 2020;Yin et al, 2020;Yoo et al, 2019). Consistently, in the current study, we found that remifentanil significantly suppressed intestinal I/R-induced oxidative stress, as evidenced by decreased intestinal mucosal MDA and increased intestinal mucosal SOD levels, as well as downregulated ER stress, as evidenced by the decreased mRNA and protein expressions of Bip, CHOP, caspase-12, and cleaved caspase-3 in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that MLC phosphorylation mediated by upregulated MLCK is crucial to intestinal barrier breakdown induced by hypoxia or proinflammatory cytokines[ 7 ]. Tight junctions ZO-1 and CLDN-2 regulated by the MLCK pathway are the two crucial factors regulating the intestinal barrier in I/R[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integrity of the intestinal mucosal barrier is retained by the critical factors of tight junctions and intercellular junctions, including transmembrane proteins such as zonula occludens (ZO), claudins (CLDN) and junctional adhesion molecule. These consist of a complex that forms a selectively permeable seal between adjacent epithelial cells, which is a key element in the paradigm of gut-origin MODS[ 5 , 6 ]. Myosin light chain (MLC) phosphorylation via MLC kinase (MLCK) is critical in pathophysiological modulation of intestinal mucosal barrier breakdown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of ERS caused caspase-12 to translocate from the ER to the cytoplasm, cleaved caspase-9, activated caspase-3, and finally led to apoptosis. HRS has been reported to mitigate ERS and ERS induced apoptosis resulting from I/R in multiple organs including myocardium, 48 intestinal, 49 liver, 50,51 and brain, 52 as revealed by down-regulated mRNA and protein levels of the pivotal proteins involved in ERS, such as glucose-regulated protein 78 (GRP78) and C/EBP homologous protein (CHOP). According to the results of research by Sun et al, HRS treatment could alleviate the elevated GRP78, CHOP and X-box binding protein-1mRNA expression induced by hyperoxia exposure, hinting that hydrogen could significantly reduce hyperoxic acute lung injury in rats by inhibiting the elevation in ERS.…”
Section: Hydrogen Inhibits Apoptotic Cascadesmentioning
confidence: 99%